Men's revealed preferences regarding women's promiscuity - Sohn, Kitae (Pergamon Press, 2016)
© 2016 Elsevier Ltd.Men have evolved to exhibit a desire for chastity and sexual fidelity and an abhorrence of promiscuity in long-term mates. We investigated whether these preferences manifest themselves even in an unlikely situation (prostitution) by observing men's behavior. We considered 8817 prostitutes under age 45 who worked in Indonesian cities in 2002-2004. We measured female promiscuity by experience in prostitution and applied OLS to determine whether clients paid more to less experienced prostitutes. After controlling for a set of characteristics of prostitutes and clients, we found that compared to prostitutes with an experience = 1 year, prostitutes with an experience of 2-4 years earned 4.2% less, and those with an experience > 4 years earned 7.7% less. The difference is great because a value of 4.2% is just under the daily expenditure per capita on food. The relationship was more pronounced for prostitutes of high fertile age and for prostitutes with greater negotiability. It seems that the preferences are strongly built in men's psychology.